Ciência e prática: ensino agrícola na educação presbiteriana em Minas Gerais (1908-1938) - Meira, José Normando Gonçalves (2009)
This research, of historical character, discusses the presbyterian education in Minas Gerais, favoring the Lavra´s experience, on west of the state, where it was founded in 1893 the Evangelical Institute (which late came to be called Gammon Presbyterian Institute). In the study of this Protestant enterprise of Calvinist tradition, reformed, it points out on the search the Agricultural College of Lavras, founded in 1908, that beside the gymnasium, with preparatory school attached, and the female school Carlota Kemper, the Commercial School and other single courses formed the Evangelical Institute. The purposes of this study are: to amplify the discussion about the protestant education in Brazil, principally in what refers to Minas Gerais; to comprehend the relationships between religious convictions and the social action , specifically in what refers to educational practice and to its implications for the society construction; to evaluate the relationships between the Presbyterian educational project in Minas Gerais and the americanism settled down on the social brazilian imaginary from the middle of 19th century; to discuss the protestant ideology brought by the north american missionaries and the efficacy of its symbols, specifically those related to scholar education to its purposes of reforming the brazilian society; to analyze the educational principles that guided the Evangelical Institute of Lavras and, specifically, its Agricultural College, in search of efficacy to its pedagogic practices; to raise the ethics and morals qualities understood as needed for the formation of the students. This research allowed comprehending the relationship between the missions purposes and the discourse of agricultural modernization in Brazil and, specifically, in Minas Gerais, by the means of scientific knowledge. It allowed the analysis of how the Presbyterian civilizating project was introduced in the context of the discussions concerning the earliest decades of the brazilian Republic as to the modernization of the country and the role of the education so that these ideals were achieved. For the research accomplishment, were used sources found at the Arquivo Público Mineiro, Museu Bi-Moreira from Universidade Federal de Lavras and Pró-memória Gammon from Instituto Presbiteriano Gammon in Lavras, Minas Gerais State